PERFORMANCE MANAGEMENT path to growth and excellence. - Venkateswara Rao, T.; Chawla, Nandini ([S.l.] : ROUTLEDGE INDIA, 2024)
This book attempts to shift focus from performance appraisals to performance management incorporating performance planning, analysis, and development as critical components of it. The performance management system (PMS) is a future-driven exercise rather than merely a past-reviewing exercise. Performance management is treated as a year-round practice and not an appraisal process conducted once a quarter or annually. Moreover, it is now considered to be everyone's responsibility and not merely that of HR or the upper management. This book advocates the structuring of PMSs and their implementation. It incorporates the most modern 360-degree feedback systems and shows the ways and means of integrating it into PMS. Arguments are offered to use rating-less appraisals and/or a combination of appraisals with 360-degree feedback. It defines performance management to mean continuous improvements in performance of individuals, their teams, departments, and corporations. It also outlines that planning, analysis, review, coaching, and capability building are essential building blocks for good performance management. Concise, lucid, and engaging, this volume would be useful to the students, researchers, and faculty of human resource management, organizational behaviour and applied psychology. It would also be an invaluable guidebook for practicing business executives and HR professionals to help them implement the performance management system for effective talent management leading to increased productivity.
Keywords: BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Training; Employees -- Rating of; Performance -- Evaluation